Intellectual property, trade, human rights and access to medicines in Africa: A Reader - Akonumbo, Atangcho N (Pretoria University Law Press (PULP), 2022)
Intellectual property, trade, human rights and access to medicines in Africa: A reader by Atangcho N Akonumbo explores the current debates and conflicts pertaining to intellectual property (IP), trade and access to medicines in Africa as a public health issue, in a public health context. The Reader has a broad focus running across fourteen chapters. It examines the complex web of access to medicines, while introducing major concepts pertaining to access to medicines such as IP, trade, medicine and human rights, and provides a historical overview of the nexus between IP and human rights. It establishes the link between human rights, IP and access to medicines within the context of developing countries broadly and Africa in particular. The Reader discusses key flexibilities within the international IP framework championed by the TRIPS Agreement to enhance access to medicines, including compulsory licensing and parallel importation, while addressing impediments therein which provoked the Doha Declaration and arrangements thereafter. Also, it examines issues such as the implications of data exclusivity and linkage techniques; the role of anti-counterfeiting and competition laws in checking the effect of IP regimes; current threats to access to medicines at the international, regional and national levels such as the influence of regional or bilateral trade agreements; and research and development in respect of medicines for neglected and (re)emerging infectious diseases. It discusses the contributions of naturopathic and traditional medicines as parallel and complementary systems to modern medicine in the access to medicines landscape in the African context. The Reader further addresses the implications of the difficulty of access to medicines for women, children and other social minorities such as disabled persons and Lesbian, Gay, Bisexual, and Transgender (LGBT) persons. This Reader comes at a critical time, and potentially, a turning point in the history of public health crisis in Africa - when concerns about access to medicines have been heightened in the face of (re)emerging diseases and today the Covid-19 pandemic - a situation which has revealed gross lapses in public health governance. It is written in a simple language, making its content accessible to a wide audience. It contains informative and useful graphs, text boxes and illustrative excerpts from various primary and secondary sources. The Reader is likely to become an invaluable tool for a wide range of persons and institutions, including academics, students, legal practitioners, health professionals, drug procurement agencies, civil society organisations and the public at large, involved or interested in the access to medicines discourse.